2015
DOI: 10.3892/etm.2015.2703
|View full text |Cite
|
Sign up to set email alerts
|

Modular flexible ureteroscopy and holmium laser lithotripsy for the treatment of renal and proximal ureteral calculi: A single-surgeon experience of 382 cases

Abstract: To determine the safety and efficacy of modular flexible ureteroscopy and holmium laser lithotripsy for the treatment of renal and proximal ureteral calculi, a retrospective chart review of a single surgeon's 3-year modular flexible ureteroscopy experience was performed. All of the patients were treated with modular flexible ureteroscopy and holmium laser lithotripsy by a single surgeon. Stone-free status was defined as no fragments or a single fragment ≤4 mm in diameter at the 3-month follow-up. The procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Particularly in group H, the stage I clearance rate was slightly lower than the approximately 80% reported in other literature works. 11 , 12 This may have been due to the stricter criteria for residual stones defined in the present study and the fact that stone fragments drifted into the kidneys in dispersed locations and were more difficult to retrieve. Therefore, in addition to reducing the incidence of stone displacement and residual stone fragmentation, the previously described characteristics of “suction while fighting, fragmentation and clearing in one step” in group U were also advantageous in terms of the stone clearance rate due to the lower conversion rate of flexible ureteroscopy.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Particularly in group H, the stage I clearance rate was slightly lower than the approximately 80% reported in other literature works. 11 , 12 This may have been due to the stricter criteria for residual stones defined in the present study and the fact that stone fragments drifted into the kidneys in dispersed locations and were more difficult to retrieve. Therefore, in addition to reducing the incidence of stone displacement and residual stone fragmentation, the previously described characteristics of “suction while fighting, fragmentation and clearing in one step” in group U were also advantageous in terms of the stone clearance rate due to the lower conversion rate of flexible ureteroscopy.…”
Section: Discussionmentioning
confidence: 86%
“…Particularly in group H, the stage I clearance rate was slightly lower than the approximately 80% reported in other literature works. 11,12 This may have been due to the stricter criteria for residual stones defined in the present study and the fact that stone fragments drifted into the kidneys in dispersed locations and were more difficult to retrieve. Therefore, in addition to reducing the incidence of stone displacement and residual stone fragmentation, https://doi.org/10.2147/IJGM.S325306…”
Section: Discussionmentioning
confidence: 88%
“…Bu cihaz, tekrar kullanıla-bilir bir optik kablo, bir ışık kablosu, çalışma kanalı ve bir kumanda mekanizması ile birlikte kanalları olan tek kullanımlık multilümen endoskopik bir kateterden oluşmaktadır (Resim 4). Polyscope ile yapılan ilk sonuçlar, cihazın teşhis ve terapötik URS için güvenli ve etkili olduğunu, üriner taşların 3 cm'ye kadar olan kısmının tedavisi de dahil olmak üzere önerilebileceğini göstermektedir (19)(20)(21)(22). Maliyeti düşürmek için tek kullanımlık fleksibl URS'lerin tekrar steril edilerek de kullanılabileceği bildirilmiştir (21).…”
Section: Tek Kullanımlık Fleksibl Urs'lerunclassified
“…Ureteroscopy revealed that the left calculus was located in the left lower segment ureter ~0.5 cm from the left ureteral orifice. The calculus was subsequently fragmented with a holmium laser as previously described (16). The left ureter was completely twisted to the right side and so the ureteroscope was unable to move forward any further following intracorporeal lithotripsy.…”
Section: Management Of Uppermentioning
confidence: 99%